The Opposition of the Middle and the Higher Vowels in the Last Syllable of the Dialect of Akmenė - Murinienė, Lina (Kalbotyra, 1997)
The article deals with the peculiarities of the contrast of the middle vowels ẹ, ọ and the higher i, u in the last syllable of the North Žemaitian dialect of Akmenė. The above area is sometimes treated as an exclusive edge of the said dialed with a very peculiar vocalism not found in other North Žemaitian dialects, for example, with the absence of the contrast of i, u and ẹ, ọ in the last syllable. The statistical and experimental analysis has proved: a) the existence of regular phonological opposition of the said vowels; b) the consistent dependence of the realization of the middle or the higher vowels upon the origin of the vowel of the last syllable. The realization of the higher vowels i, u is especially systematic. The realization of the ẹ, ọ vowels is systematic, too, but not so consistent. The seeming irregularities of the realization of the middle vowels are mostly determined by the tendency of progressive assimilation.